Organic Syntheses 2003
DOI: 10.1002/0471264180.os044.06
|View full text |Cite
|
Sign up to set email alerts
|

t ‐Butyl azidoformate

Abstract: t ‐Butyl azidoformate product: t ‐Butyl azidoformate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…50 The cycloaddition reaction is performed under relatively mild conditions starting from pristine MWCNTs and the freshly prepared tert-butyl azidoformate. 41 The tert-butyloxycarbonylaziridino-MWCNT (MW@N BOC ) intermediate undergoes 51 a thermal treatment under ultrahigh vacuum that readily and selectively decomposes the carbamate units into isobutene and CO 2 and leads to the target aziridine-NH-functionalized sample (MW@N Az ) (Scheme 1). 50 At odds with other covalent functionalization protocols where basic N-containing groups can be grafted to the surface of complex carbon structures as dangling arms, 11,12 the [2 + 1] nitrene cycloaddition guarantees a more intimate connection between the exohedral N-dopant and the sp 2 carbon network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…50 The cycloaddition reaction is performed under relatively mild conditions starting from pristine MWCNTs and the freshly prepared tert-butyl azidoformate. 41 The tert-butyloxycarbonylaziridino-MWCNT (MW@N BOC ) intermediate undergoes 51 a thermal treatment under ultrahigh vacuum that readily and selectively decomposes the carbamate units into isobutene and CO 2 and leads to the target aziridine-NH-functionalized sample (MW@N Az ) (Scheme 1). 50 At odds with other covalent functionalization protocols where basic N-containing groups can be grafted to the surface of complex carbon structures as dangling arms, 11,12 the [2 + 1] nitrene cycloaddition guarantees a more intimate connection between the exohedral N-dopant and the sp 2 carbon network.…”
Section: Resultsmentioning
confidence: 99%
“…The adopted procedure for the N-decoration is based on a two-step protocol that includes a nitrene [2 + 1] cycloaddition to the π-electron system of MWCNTs followed by a controlled thermal decomposition of the reaction product . The cycloaddition reaction is performed under relatively mild conditions starting from pristine MWCNTs and the freshly prepared tert -butyl azidoformate . The tert -butyloxycarbonylaziridino-MWCNT ( MW@N BOC ) intermediate undergoes a thermal treatment under ultrahigh vacuum that readily and selectively decomposes the carbamate units into isobutene and CO 2 and leads to the target aziridine-NH-functionalized sample ( MW@N Az ) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of alkali salts (one equiv.) had a positive effect on the conversion with K 3 PO 4 being superior to other potassium salts (entries [8][9][10]. While an increase of the BocN 3 equivalents had no effect on the conver-sion (entry 11), it was shown that the reaction could be promoted even with 0.5 equiv.…”
mentioning
confidence: 99%
“…BocN 3 , which is known to be a potential explosive, was employed in crude form without prior distillation. [9,10] Under identical conditions, 3-pyridin-2-ylthiophenes were subjected to the amination reaction. If the 2-position was available for C À H activation a facile amination was observed, which delivered the Boc-protected 2-aminothiophenes 3a and 3b in high yields ( Figure 1).…”
mentioning
confidence: 99%